2014
DOI: 10.1039/c3dt52869c
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of high temperature hexagonal phase of SrAl2O4 at room temperature: role of ZnO

Abstract: Strontium aluminate (SrAl2O4) exhibits a monoclinic structure at room temperature (RT) and transforms to a hexagonal structure at above 650 °C, reported previously in the literature. In this article, we have shown a stable, high temperature hexagonal phase of SrAl2O4 (SAO) at RT by synthesizing a SAO-ZnO composite through a combustion technique. While SAO crystallizes in the monoclinic phase by adding 2.5 wt% of ZnO, a stable hexagonal phase of SAO at RT has been obtained for 20 wt% of ZnO. Further, the hexago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
18
1
2
Order By: Relevance
“…There is an inconsistency in the results reported regarding the luminescence of this host doped; the vast majority reported that only the monoclinic structure exhibits luminescent properties, whereas another revealed higher emission intensity with the hexagonal polymorph . There are few works about hexagonal phase due to the fact that formation of this metastable phase at room temperature is quite difficult; being obtained only by solidification from the high‐temperature liquid state by firing at 900–1300°C with low contents of Ca 2+ , Ba 2+ , or Al 3+ excess or by synthesizing a SAO–ZnO composite through a combustion technique …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an inconsistency in the results reported regarding the luminescence of this host doped; the vast majority reported that only the monoclinic structure exhibits luminescent properties, whereas another revealed higher emission intensity with the hexagonal polymorph . There are few works about hexagonal phase due to the fact that formation of this metastable phase at room temperature is quite difficult; being obtained only by solidification from the high‐temperature liquid state by firing at 900–1300°C with low contents of Ca 2+ , Ba 2+ , or Al 3+ excess or by synthesizing a SAO–ZnO composite through a combustion technique …”
Section: Introductionmentioning
confidence: 99%
“…[13] There are few works about hexagonal phase due to the fact that formation of this metastable phase at room temperature is quite difficult; being obtained only by solidification from the high-temperature liquid state by firing at 900-1300°C with low contents of Ca 2+ , [14] Ba 2+ , [15] or Al 3+ [16] excess or by synthesizing a SAO-ZnO composite through a combustion technique. [17] Herein, we have synthesized SrAl 2 O 4 powder via a molten salt method in order to obtain at room temperature the monoclinic and hexagonal polymorphs. The purpose of adopting this route in the present investigations is due to the fact that this innovative process induces an increase in the reaction rate and a reduction of the formation temperature of SrAl 2 O 4 in comparison with the classic solid-state method.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have shown that ZnO(%)-SAO composite, calcined at 700 C, with increasing concentration of ZnO from 0 to 20%, monoclinic phase of SAO transforms to hexagonal phase at 20% of ZnO. 25 Further, we have demonstrated that with increasing calcination temperature from 700 C to 1200 C, hexagonal phase again transforms to monoclinic. 25 Moreover, XRD pattern of ZnO(20%)-SAO composite calcined at 700 C named as composite(A) shows wurtzite structure of ZnO (P6 3 mc) and the hexagonal phase (P6 3 22) of SAO.…”
Section: Resultsmentioning
confidence: 82%
“…20 wt% of ZnO was dispersed in SrAl 2 O 4 matrix and the above composite was calcined at 700 C and 1200 C. Detailed description of synthesis of composites was given elsewhere. 25 ZnO, SrAl 2 O 4 and ZnO(20%)-SrAl 2 O 4 composite calcined at 700 C and 1200 C were denoted as ZnO(A) and ZnO(B); SAO(A) and SAO(B); composite(A) and composite(B) respectively throughout the manuscript. We characterized the material using UV-visible spectrophotometer, photoluminescence (PL) spectroscopy and thermoluminescence (TL) spectroscopy.…”
Section: Synthesis and Characterizationsmentioning
confidence: 99%
“…In addition, in MAl 2 O 4 matrix, the M 2+ is located in the interior of [AlO 4 ] 5− tetrahedral and occupies the position of two low symmetries and coordination [9,10] . The defects based upon Eu 2+ 2+ , Ca 2+ and Ba 2+ ) phosphors have the highest luminescence intensity and longest afterglow time [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%